El impacto de la revalorización de ganado vacuno a valor neto de realización sobre la utilidad en la hacienda Antonio José. - Bedón Tipán, Luisa Natali (2020)
The present research analyzes the revaluation processes through the method of net valve of realization, whose purpose of study is the cattle, specifically the diary production cattle in the Antonio Jose Farm. The investigation was done in quantitative way, where it was analyzed numerical data and qualities of biological assets where it was applied techniques such as: Interview and observation, finally the comparative method was used to calculate the revaluation that allowed equate the inspected good with similar goods, that is, comparing biological assets with other ones of equal characteristics. While doing an analysis it was identified that six cows got in the process of revaluation, where these six biological assets are still in process of production with a new real valve recalculated .However, this method was applied to the assets that have finished their productive life and those that were written off in the books, and later they were revalued by means of a report issued by the zootechnical veterinarian of the farm. In conclusion, it can be mentioned that the revaluation process has identified again as it is shown in the results obtained, and that are reflected with a variation of 7,88% with an increase of $ 8.184,20 recalculated valves, they give a result in the financial statements a profit of $ 6.378,20 increasing net worth, considering these data it is necessary that Antonio José farm perform revaluation processes in cattle at the end of their productive life acquiring a new valve according to the market price, allowing the improvement of the accounting records and the decision making for a better functioning of the farm.